Early use of partial acrylic denture obturator in the postoperative treatment of bone defects after marsupialisation of large jaw cysts - Jovanović Marija; Stojanović Simona; Todorović Kosta; Obradović Radmila; Igić Marko; Stojković Branislava; Gligorijević Nikola; Spasić Milan; Jovanović Goran (Medicinski fakultet i Klinika za stomatologiju, Niš, 2019)
Introduction: After marsupialisation of large jaw cysts, there comes to the formation of bone defects which do not guarantee the stability of the blood clot and therefore are filled with iodine gauze. Any replacement of iodine gauze, toilet of the wound, causes minor or major bleeding, which slows wound epithelialisation and organization. Therefore, making the partial acrylic denture obturator is recommended to be done a few weeks after the surgery. Case report: This work presents two patients who had partial acrylic denture obturator made on the tenth day after the surgery. This allowed significantly easier toilet of the wounds, faster epithelialization and organization, and thus faster bone healing. Conclusion: Restored function of chewing, swallowing and speech, as well as the aesthetic appearance suggest that early use of acrylic obturator prosthesis is very significant.